Model Ekspansi Kapasitas yang Mempertimbangkan Persaingan Duopoli dan Inovasi Teknologi Untuk Horison Perencanaan Terbatas, Studi Kasus: Jaringan Akses Kabel Telekomunikasi - Farham H. M. Saleh (Teknoin, 2005)
The changes of market structure from monopoly to duopoly is proposed to introduce the competition to the company. In the new market structure, duopoly, the company must be establish the competitive strategy that could be implemented and then establish the best competitive strategy. This research addresses the problem of capacity expansion, i.e., to formuate a capacity expansion model for a local access cable broadband telecommunication network. The model covers the market structure, duopoly, and the technologicai innovation. In the model, the market structure was represented by the market leader and market chalenger, while the technological innovation was represented by the rate of technological innovation paramater. Market leader was established three competitive strategy, i.e., preemptive defense, position defense, and counteroffensive defense, while market challenger was established two competitive strategy, i.e., encirclement attack and frontal attack.The model was optimized by the first derivative. Numerical experience and analysis are shown in this paper.Keywords: capacity expansion, local access cable telecommunication network, duopoly market, technological innovation.